Earwig and the witch - Jones, Diana Wynne. (Greenwillow Books, 2012)
Although an orphan, Earwig has always enjoyed living at St. Morwald's, where she manages to make everyone do her bidding, but when she is taken in by a foster parents who are actually a witch and a demon, she has a hard time trying to turn the situation to her advantage.